EnRank: An Ensemble Method to Detect Pulmonary Hypertension Biomarkers Based on Feature Selection and Machine Learning Models - Liu, Xiangju; Zhang, Yu; Fu, Chunli; Zhang, Ruochi; Zhou, Fengfeng (Frontiers in Genetics, 2021)
Pulmonary hypertension (PH) is a common disease that affects the normal functioning of the human pulmonary arteries. The peripheral blood mononuclear cells (PMBCs) served as an ideal source for a minimally invasive disease diagnosis. This study hypothesized that the transcriptional fluctuations in the PMBCs exposed to the PH arteries may stably reflect the disease. However, the dimension of a human transcriptome is much higher than the number of samples in all the existing datasets. So, an ensemble feature selection algorithm, EnRank, was proposed to integrate the ranking information of four popular feature selection algorithms, i.e., Ttest, Chi2, Ridge and Lasso. Our results suggested that the EnRank-detected biomarkers provided useful information from these four feature selection algorithms and achieved a very good prediction accuracy in predicting the PH patients. Many of the EnRank-detected biomarkers were also supported by the literature.